Manual therapy versus therapeutic exercise in non-specific chronic neck pain: study protocol for a randomized controlled trial - Bernal-Utrera, Carlos; González-Gerez, Juan José; Saavedra-Hernandez, Manuel; Lérida-Ortega, Miguel Ángel; Rodríguez-Blanco, Cleofás (Current controlled trials in cardiovascular medicine, 2019)
The underlying mechanisms of non-specific chronic neck pain relapses are not clear, but they could be associated with a deficit and alteration of neck muscles propioception that play a decisive role in cervical joint position, motor control of the head, and postural stability. Numerous treatments for non-specific chronic neck pain have been described in the scientific literature. However, few studies analyze its influence on postural stability, since these alterations are not fully described, and various theories emerge about the reasons that cause it. Our primary aim is to analyze the differences in postural stability, pain, cervical disability, and the relation between them produced by a treatment based on manual therapy and another based on therapeutic exercise. The short-term and mid-term changes produced by different therapies on subjects with non-specific chronic neck pain will be studied. The sample will be randomly divided into three groups: manual therapy, therapeutic exercise, and placebo. As dependent variables of the study, we will take (1) Overall Balance Index, measured through a dynamic stabilometric platform; (2) pain, based on the visual analog scale and the Pressure Pain Threshold; (3) cervical disability, through the neck disability index. The findings will be analyzed statistically considering a 5% significance level (p ≤ 0.05). Our study aims to provide knowledge about postural stability and its relationship with pain in subjects with non-specific chronic neck pain. Analyzing the results produced by different types of therapy will allow us to draw conclusions about the mechanisms, structural or central, that may elicit these alterations. Brazilian Clinical Trials Registry, RBR-2vj7sw . Registered on 28 November 2018.